Insulin-like growth factor-1 and growth in infants 0-6 months of age - Maria Mexitalia; Bob Kevin Pardede; Agustini Utari (Indonesian Pediatric Society, 2021)
Background During infancy, growth is affected by many factors, including hormones. Insulin-like growth factor-1 (IGF-1) is a hormone with an important role in regulating somatic growth and organ development. Objective To analyze for possible correlations between IGF-1 levels and infant growth from 0-6 months of age. Methods A prospective study was conducted on 38 infants from birth to 6 months of age. Inclusion criteria were full-term newborns with normal birth weight and singleton birth. Serum IGF-1 was measured twice, from umbilical cord blood at birth and at 6 months of age. Anthropometric measurements were made every three months. Paired T-test was used to analyze mean IGF-1 among time points, and Pearson’s correlation test was used to analyze IGF-1 levels and growth. Results Mean IGF-1 level decreased from birth to 6 months of age (89.6 ng/mL vs. 48.3 ng/mL, respectively; P<0.001). Delta IGF-1 had positive significant correlations with delta weight at 3 months (r=0.347; P=0.033) and 6 months (r=0.386; P=0.017), as well as delta head circumference at 3 months (r= 0.356; P=0.028) and 6 months (r=0.357; P=0.028). However, there were significant negative correlations between umbilical cord IGF-1 with delta body weight (r= −0.459; P=0.004) and delta length at 6 months (r= −0.414; P=0.010). Conclusions. There iss a decrease in IGF-1 levels at the first 6 months of life. Umbilical cord IGF-1 level has negative correlations with the weight and length increment at the age of 6 months.